(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
This paper describes the barriers to the development of renewable energies, and then a review of the literature on the entry barriers of renewable energies in each of the Southern Common Market (Mercosur) countries with the objective of identifying the obstacles to development and integration of new sources of renewable energy in the regional trade bloc.